Real Option Approach to R & D Project Valuation - Song, Shao Rong (2006)
The thesis illustrates that traditional NPV and decision tree are not appropriate to value the R&D project, due to the high uncertainty and multi-phase characters. The thesis reviews the applicability of real option methods in this field and explains the real options pricing theory. Additionally, we construct a hypothetical case of new drug development and show the failure of Expected NPV application in capturing managerial flexibility. Based on real options theory, the paper also advances a general real option analysis framework of R&D investment. Moreover, we point out that the value of R&D project is the sum of value calculated by ENPV and the option value. According to this application framework, the thesis revalues the hypothetical project of new drug development, identifying main real options inherent in this project. In order to accurately evaluate value of the new drug development, based on analyzing real options pricing theory and summing up the features of R&D project, two continuous time models (Black-Scholes and Margrabe) and one discrete time model (Modified binomial lattice) will be applied to find value of the project's options. Based on the big difference among computing results, we can conclude that the modified binomial lattice model may be the most appropriate to value the R&D project.